Respuesta :
The answer is g(x)=(x-6)(2x-1).hope this helps please add brainlist
![Ver imagen fatoumata1288p2mm26](https://us-static.z-dn.net/files/dd8/189dd924700df8cac28851e98c470775.png)
Answer:
[tex]\boxed{g(x) = (x - 6)(2x - 1)}[/tex]
Step-by-step explanation:
An x-intercept is the value of x when g(x) = 0. So, for each function, we must set g(x) = 0 and solve for x.
(a) g(x) = 2(x + 1)(x + 6) = 0
x + 1 = 0 x + 6 = 0
x = -1 x = -6
Wrong.
(b) g(x) = (x - 6)(2x - 1)
x - 6 = 0 2x – 1 = 0
x = 6 2x = 1
x = ½
Right.
(c) g(x) = 2(x - 2)(x - 6)
x - 2 = 0 x - 6 = 0
x = 2 x = 6
Wrong.
(d) g(x) = (x + 6)(x + 2)
x + 6 = 0 x +2 = 0
x = -6 x = -2
Wrong.
The only function that has x-intercepts at (½, 0) and (6, 0) is
[tex]\boxed{g(x) = (x - 6)(2x - 1)}[/tex]